A CLINICAL EVALUATION OF MRUDVIKADI KASHAYAM IN MADATYAYA (International Journal of Ayurveda and Pharma Research, 2017)
In the current scenario; alcohol addiction is one of the major problems faced by the society. As a doctor it is our responsibility to help such alcohol addicts by counseling and treating them to recover from this addiction. It was with this intention that the disease Madatyaya has been chosen for the study.A study was conducted to access clinical efficacy of Mrudvikadi Kashayam . 20 patients of Madatyaya were selected in control group and 20 patients in trial group by random selection method. Control group was not given any medicine; however they were observed for 28 days for all parameters. Trial group patients were administered Mrudvikadi Kashayam in the dose of 80ml with Jala (water) in 2 divided dose,morning and evening after food for the duration of 28 days. Gradation scale was used for the purpose of case taking; however at the time of statistical analysis Wileoxan test, Mann-Whitney test, Paired t-test, Unpaired t-test were used. It revealed that Mrudvikadi Kashayam is effective in Madatyaya. It significantly reduces the symptoms Daurbalya, Nidranash, Aruchi, Chhardi, Hrullas, Parshwashoola, Shwasa, Murcha, Gaurava and Shirokampa. It increases the Haemoglobin value and lowers the LFT levels in the patients of Madatyaya.Mrudvikadi Kashayam is Balya, Rasayana and Pachana, and enhanced the nutritional status of such alcoholic patients. Also appetite and metabolism is increased due to its Deepan karma, which directly affects the Hb level in patients. As Pippali, Yashtimadhu, possesses Vishghna property, Mrudvikadi Kashayam de-toxified the toxic effects of Madya on Liver thus helpful in lowering LFT values.